Optimization of cellulose nanofiber loading and processing conditions during melt extrusion of poly(3-hydroxybutyrateco-3-hydroxyhexanoate) bionanocomposites - Shazleen, Siti Shazra; Sabaruddin, Fatimah Athiyah; Ando, Yoshito; Ariffin, Hidayah (Multidisciplinary Digital Publishing Institute, 2023)
This present study optimized the cellulose nanofiber (CNF) loading and melt processing conditions of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) P(HB-co-11% HHx) bionanocomposite fabrication in twin screw extruder by using the response surface methodology (RSM). A face-centered central composite design (CCD) was applied to statistically specify the important parameters, namely CNF loading (1–9 wt.%), rotational speed (20–60 rpm), and temperature (135–175 ◦C), on the mechanical properties of the P(HB-co-11% HHx) bionanocomposites. The developed model reveals that CNF loading and temperature were the dominating parameters that enhanced the mechanical properties of the P(HB-co-11% HHx)/CNF bionanocomposites. The optimal CNF loading, rotational speed, and temperature for P(HB-co-11% HHx) bionanocomposite fabrication were 1.5 wt.%, 20 rpm, and 160 ◦C, respectively. The predicted tensile strength, flexural strength, and flexural modulus for these optimum conditions were 22.96 MPa, 33.91 MPa, and 1.02 GPa, respectively, with maximum desirability of 0.929. P(HB-co-11% HHx)/CNF bionanocomposites exhibited improved tensile strength, flexural strength, and modulus by 17, 6, and 20%, respectively, as compared to the neat P(HB-co-11% HHx). While the crystallinity of P(HB-co-11% HHx)/CNF bionanocomposites increased by 17% under the optimal fabrication conditions, the thermal stability of the P(HB-co-11% HHx)/CNF bionanocomposites was not significantly different from neat P(HB-co-11% HHx).